Dampak Pandemi COVID-19 terhadap Pemanfaatan MUYAN KB Tahun 2020 - Lidya Dwijayani (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
Background: Determination of the national emergency status of COVID-19 in Indonesia since March 31, 2020 has caused people’s accessibility to get contraceptive service with MUYAN KB to decline; this is one of the factors decreasing the achievement of new family planning participants nationally. Method: This study is a descriptive study with secondary data analysis of data belonging to the Central BKKBN, the data collection technique used in literature research. Result: The decline in the movement of MUYAN KB occurred in April 2020 (46%), the largest decrease was in November 2020, namely 76% compared to the previous year. The decline in the movement of MUYAN KB has led to a decrease in the number of new family planning participants since April 2020 (12,25%) and May 2020 (8,67%). Discussion: The decline in the role of MUYAN KB during the COVID-19 pandemic is in accordance with PSBB policy issued by the central government. This effort was made in order to prevent the transmission of COVID-19 that might from mobile family planning services using MUYAN KB. This decline needs to be anticipated by the managers of the family planning program. Conclusion: A new adaptation era family planning service mechanism is needed so that the level of contraceptive use does not decrease dramatically and its implementation remains in accordance with health protocols during the COVID-19 pandemic, such as the use of tele registration, use of online communication to counseling provision of PPE for health workers and increasing the role of PLKB/PKB to distribute emergency contraceptive likes birth control pills and condoms. Keywords: COVID-19, Mobile Family Planning Service, MUYAN KB, PLKB/PKB